Analisa Sumbu Z Pada Proses Kalibrasi Dan Pergerakan Mesin Cnc Router - Nayorama, Feriagam, Bambang Waluyo F, ST. MT, Joko Sedyono, Ph.D (2016)
The aim of this research is to know the calibration of z axis in cnc router machine and to know the acuration of declension movement to the work thing before and after being calibrated in cnc router mechine. The research prosess used acrylic which is done in three work thing, After that the calibration process is done in cnc router machine and did in the depth declension of z axis to find the accuration level in cnc router machine. The result of cnc router machine experiment, before calibration is obtained the standar data of standar deviation of the smallest 4 equilateral square is 0,0856 mm and the biggest is 0,0547 mm and 0,2937 mm and the smallest rectangle is 0,0714 mm and the biggest is 0,5740 mm and after being calibrated the data of standard deviation of the smallest 4 equilateral square is 0,0648 mm and the biggest is 0,0141 mm in the circle 0,0223 mm and 0,0223 mm and the smallest rectangle is 0,0387 mm and the biggest 0,0173 mm. the accuration level can be seen from the table before calibrated and after calibrated and it can be concluded that the result of calibration is better than the result before calibrated. Keywords: Z-axis, CNC Router, Calibration, CAD / CAM